Deformation of lamellar TiAl alloys by longitudinal twinning. (June 2016) - Edwards, Thomas Edward James; Di Gioacchino, Fabio; Muñoz-Moreno, Rocío; Clegg, William John
Abstract: The occurrence of longitudinal twinning in the engineering alloy Ti-45Al-2Nb-2Mn (at.%)-0.8 vol.% TiB2 has been studied by measuring the changes in crystallographic orientation within individual lamellae during microcompression. Twinning in this alloy appeared to be a nucleation-limited process with the twins growing from lamellar boundaries at resolved shear stresses as low as 100 MPa, consistent with observations elsewhere. However, instead of forming twins 10–200 nm in thickness, as in polysynthetically twinned crystals, the longitudinal twins in this alloy were initiated at a lamellar boundary and then spread through the whole lamella. Graphical abstract: